(untitled) (Journal of Hama University, 2026)
This study aims to review the banking accounting literature on the non-discretionary determinants of Loan loss provisions, with the aim of identifying these determinants and their measurement methods. The review included twenty-five studies published between 1994 and 2024 in peer-reviewed journals or academic research. The results of the review revealed significant variation in variables and their measurement methods across studies. The non-discretionary determinants were classified into five main categories: credit quality, credit volume, prior provisions, bank characteristics, and macroeconomic variables. The results also indicated that the most common determinant is non-performing assets, and there was little reliance on macroeconomic variables. The study suggested conducting further critical studies to develop a unified framework for modeling provisions.